A New Ferric Chloride Modified Kaolin Coagulant and Its Application in Treatment of Methylene Blue Wastewater - Ma, Q.L.; Lu, X.F.; Ma, J.C.; Gao, L.; Bao, W.R.; Ma, H.Z. (Asian Journal of Chemistry, 2015)
In this study, a new coagulant, ferric chloride modified kaolin (Fe-Kaolin) was used to treat the simulated methylene blue wastewater. The coagulant was characterized by powder X-ray diffraction and scanning electron microscopy. The effects of parameters, such as initial pH, coagulant dosage and dye concentration on methylene blue removal were also studied and the procedure was inspected by ultraviolet visible spectroscopy and chemical oxygen demand. The results showed that a maximum color and chemical oxygen demand removal efficiency of 99.64 and 90 %, respectively, for 0.12 g/L methylene blue wastewater were observed. Moreover, the environmental effect of the treated effluent was also studied.